CdSiP2 Optical Parametric Oscillator Pumped by a Nanosecond Ho:LLF Laser at 2.06 µm with Non-Collinear Phase-Matching - Marcin Piotrowski; Gerhard Spindler; Achille Bogas-Droy; Anne Hildenbrand-Dhollande (Photonics)
We report on a nanosecond-pulsed CdSiP2 (CSP) optical parametric oscillator (OPO) pumped by a Q-switched 2.06 µm Ho:LiLuF4 (Ho:LLF) laser in a compact linear cavity with a 10 mm long crystal. Utilizing a non-collinear type-I phase-matching configuration, the OPO achieved an average output power exceeding 3 W in the mid-IR region with good beam quality. The idler and signal waves can be tuned in a wide range of 3.5–4.7 µm by pump tilt and crystal rotation.